Headlines in the Kurdish news websites (A descriptive study for the headlines): A descriptive study for the headlines - Mohammed, Nozad Sidiq; Ali, Bahroz Rasul (Halabja University Journal, 2019)
This study aims to explorer the negative and positive sides of headlines in the Kurdish news websites. It display many results mainly some positive properties in the headlines of the Kurdish news sites like the neutrality of editing headline, lack of mixing the news editors' personal view in editing the news as well as other positive aspects such as finding harmony between headlines and news contents. In other word, the headline expresses the news contents among the study sample of headlines.Apart from those positive aspects, the study shows different negatives sides of the headlines in the study sample; mainly lack of using all types of headlines in the Kurdish news websites. Types of headlines restricted in a number of headline types, and this considers as a problematic for the variety that can be stemmed from the lack of professional and academic ability of the news editors.